Why Do We Need Computational Models of Psychological Change and Recovery, and How Should They Be Designed and Tested? - Mansell, Warren; Huddy, Vyv (Frontiers in Psychiatry, 2020)
Traditional research methodologies typically assume that humans operate on the basis of an ‘open loop’ stimulus-process-response rather than the ‘closed loop’ control of internal state. They also ‘chunk’ or average behavioral data rather than assess it dynamically, and they draw inferences about the working of an individual from statistical group effects. As such, we propose that they are limited in their capacity to accurately identify and test for the mechanisms of change within psychological therapies. As a solution, we explain the advantages of using a closed loop functional architecture, based on an extended homeostatic model of the brain, to construct working computational models of individual clients that can be tested against real-world data. Specifically, we describe tests of a perceptual control theory account of psychological change that combines the components of negative feedback control, hierarchies, conflict, reorganization and awareness into a working model of psychological function, and dysfunction. In brief, psychopathology is proposed to be the loss of control experienced due to chronic, unresolved conflict between important personal goals. The mechanism of change across disorders and different psychological therapies is proposed to be the capacity for the therapist to help the client shift and sustain their awareness on the higher level goals that are driving goal conflict, for sufficiently long enough to permit a trial-and-error learning process, known as reorganization, to ‘stumble’ upon a solution that regains control. We report on data from studies that have modelled these components both separately and in combination, and we describe the parallels with human data, such as the pattern of early gains and sudden gains within psychological therapy. We conclude with a description of our current research program that involves the following stages: (1) construct a model of the conflicting goals that are held by people with specific phobias; (2) optimize a model for each individual using their dynamic movement data from a virtual reality exposure task (VRET); (3) construct and optimize a learning parameter (reorganization) within each model using a subsequent VRET; (3) validate the model of each individual against a third VRET. Applications to robotics, attachment dynamics and neuroimaging are discussed.